Changes in anthropometrical status, body composition and basal metabolic rate of paediatric cancer patients during initial intensive onco-chemotherapy therapy - Kellerman, Ilde-Marie (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNutr)--Stellenbosch University, 2021.